Ginásios vocacionais: memórias e resistências (1962-2018) - Silva, Alessandra Bastos da (2020)
The objective of this research is problematize the history and memory about SEV - Serviço de Ensino Vocacional, an experience of singular teaching in history of public education happened in the state of São Paulo during 1960. Through interviews with some members of the movement GVive - Associação dos Ex Alunos, Ex Colaboradores e Amigos do Sistema Vocacional do Estado de São Paulo. An association made up of former members of Vocational’s Gym, people from the moviment, intending to analyze how these subjects build certain memories about the educational experience and how their experiences come together to create GVive in 2005. I will problematize under what circunstancies they build the moviment, what are your objectives, as well as the conflicts that permeate their existences. Besides that we will investigate how the memory was build during the years by the subjects somehow was part of the teaching experience. With the bibliography already written about the topic we will problematize the contradiction found in SEV’s story - Serviço de Ensino Vocacional.